Old City Hall on School Street, ca. 1960 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east of Old City Hall, located on School Street at City Hall Avenue. The west elevation of Old City Hall faces King's Chapel Burial Ground, which is included in the lower-left corner of the photograph. The north-northeast elevation of King's Chapel, located on the northeast corner of School and Tremont Streets, lines the right side of the photograph. The facade of Old City Hall faces south-southwest towards School Street. Old City Hall designed by Gridley J. Fox Bryant and Arthur Gilman, 1862-65 4 1/2 x 6 7/16, 4 7/8 x 6 3/4 overall Photographs